Proceso de atención nutricional en paciente femenino de 55 años de edad con tumor de colon. - Alvia Mora, Mayerling Beatriz (2023)
This clinical case is based on the nutritional care process of a 55-year-old female patient with a colon tumor whose main objective is to carry out an adequate dietary-therapeutic treatment to reduce the patient's complications. Colon cancer develops in tissues of the colon or rectum, this occurs when there are changes in the DNA, known as mutations. Nutritional assessment is carried out by means of anthropometric, biochemical, clinical and dietary indicators, their nutritional status is later diagnosed, informed consent is obtained to start treatment, and intervention is made according to nutritional needs with progressive tolerance diets.